“When” Does Picture Naming Take Longer Than Word Reading? - Valente, Andrea; Pinet, Svetlana; Alario, F.-Xavier; Laganaro, Marina (Frontiers in Psychology, 2016)
Differences between the cognitive processes involved in word reading and picture naming are well established (e.g. visual or lexico-semantic stages). Still, it is commonly thought that retrieval of phonological forms is shared across tasks. We report a test of this second hypothesis based on the time course of electroencephalographic (EEG) neural activity, reasoning that similar EEG patterns might index similar processing stages. Seventeen participants named objects and read aloud the corresponding words while their behavior and EEG activity were recorded. The latter was analyzed from stimulus onset onwards (stimulus-locked analysis) and from response onset backwards (response-locked analysis), using non-parametric statistics and the spatio-temporal segmentation of ERPs. Behavioral results confirmed that reading entails shorter latencies than naming. The analysis of EEG activity within the stimulus-to-response period allowed distinguishing three phases, broadly successive. Early on, we observed identical distribution of electric field potentials (i.e. topographies) albeit with large amplitude divergences between tasks. Then, we observed sustained cross-task differences in topographies accompanied by extended amplitude differences. Finally, the two tasks again revealed the same topographies, with significant cross-task delays in their onsets and offsets, and still significant amplitude differences. In the response-locked ERPs, the common topography displayed an offset closer to response articulation in word reading compared with picture naming, that is the transition between the offset of this shared map and the onset of articulation was significantly faster in word reading. The results suggest that the degree of cross-task similarity varies across time. The first phase suggests similar visual processes of variable intensity and time course across tasks, while the second phase suggests marked differences. Finally, similarities and differences within the third phase are compatible with a shared processing stage (likely phonological processes) with different temporal properties (onset/offset) across tasks. Overall, our results provide an overview of when, between stimulus and response, word reading and picture naming are subtended by shared- versus task-specific neural signatures. This in turn is suggestive of when the two tasks involve similar vs. different cognitive processes.